2006
DOI: 10.1121/1.2216905
|View full text |Cite
|
Sign up to set email alerts
|

On the modeling of sound propagation over multi-impedance discontinuities using a semiempirical diffraction formulation

Abstract: Several approximate extensions of the semi-empirical De Jong model ͓De Jong et al., J. Sound and Vib. 86, 23-46 ͑1983͔͒ are considered for the prediction of sound propagation over multiple impedance discontinuities. A limitation in the original formulation of the De Jong model is highlighted and a modified form that overcomes this limitation is derived based on reciprocity. This leads to the development of a model for multiple impedance discontinuities that can be used for the investigation of sound-wave propa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Both surfaces are characterised by the variable porosity impedance model [10] with effective flow resistivity values and porosity change rates of 30 kPa s m −2 and 15 m −1 and 100 MPa s m −2 and 15 m −1 for the soft and hard surfaces respectively. These comparisons confirm that the modification of the de Jong method by Lam and Monazzam [24] gives predictions that are closer to those made using BEM than the original de Jong formulation particularly for the soft to hard discontinuity.…”
Section: Multiple Discontinuitiessupporting
confidence: 76%
See 1 more Smart Citation
“…Both surfaces are characterised by the variable porosity impedance model [10] with effective flow resistivity values and porosity change rates of 30 kPa s m −2 and 15 m −1 and 100 MPa s m −2 and 15 m −1 for the soft and hard surfaces respectively. These comparisons confirm that the modification of the de Jong method by Lam and Monazzam [24] gives predictions that are closer to those made using BEM than the original de Jong formulation particularly for the soft to hard discontinuity.…”
Section: Multiple Discontinuitiessupporting
confidence: 76%
“…[22] compare data from measurements over single impedance ground surface with the De Jong model predictions [21]. They show that the agreement between data and De Jong model predictions is good except when the source and receiver are placed Monazzam [24] gives predictions that are closer to those made using BEM than the original de Jong formulation particularly for the soft to hard discontinuity. …”
Section: Single Discontinuitymentioning
confidence: 93%
“…It is therefore susceptible to receiver specific interference effects caused by ground and other nearby reflections. Previous research have shown that the performance of a diffusive cover for barrier applications can be characterised by the attenuation of the sound as it propagates from one end of the cover to the other [6]. It is therefore possible to determine the performance by measuring the attenuation at the edge of the cover.…”
Section: Nearfield Testmentioning
confidence: 99%
“…Once the reflection geometry is worked out by the numerical ray tracing, the effect of the ground at each reflection can then be approximated by the Weyl-van der Pol formulation. 12,13 The height of the upper boundary of the computational grid is set using the rule of thumb of 1 / 10 of the maximum horizontal range.…”
Section: The Ray Tracing Modelmentioning
confidence: 99%